Palladium-Catalyzed Direct Arylation for the Synthesis of Indeno[2,1-b]-pyrrol-8-ones - Chang, Junbiao; Sun, Li; Dong, Jingjing; Shen, Zhenhua; Zhang, Yueteng; Wu, Jie; Wang, Ruiyong; Wang, Jinqian; Song, Chuanjun (Synlett, 2012)
Treatment of 2-bromophenyl (N-tosylpyrrol-2′-yl)-ketones with Pd(OAc)2, Ph3P, and K2CO3 resulted in the formation of indeno[2,1-b]pyrrol-8-ones in moderate to good yields.
Keywords: direct arylation; palladium catalyst; acylation; indeno[2,1-b]pyrrol-8-one; pyrroles